Uterine Cavity Irrigation With Office Hysteroscopy During Ovarian Stimulation for IVF: A Randomized Controlled Trial - Ghasemi, Marzieh; Aleyasin, Ashraf; Fatemi, Human M.; Ghaemdoust, Faezeh; Shahrakipour, Mahnaz (Frontiers in Endocrinology, 2022)
Abstract: Objective: This was a non-blinded randomized controlled study to evaluate whether endometrial irrigation via office hysteroscopy during the early follicular phase would lead to a higher level of live birth rates compared to no irrigation in the fresh embryo transfer cycle. Method: The study was conducted in Tehran university of medical sciences from June 2015 to June 2016. women under the age of 40 with primary infertility without history of previous IVF/ICSI or hysteroscopic examination, were included. Controlled ovarian hyperstimulation was done. Hysteroscopy was performed in the early mid-follicular phase of a stimulation cycle (day 5-7) with a vaginoscopy approach and saline irrigation in hysteroscopy group. Embryo-transfer was done in the same cycle. Results: 228 patients completed their participation in the study. In the fresh cycle, clinical pregnancy rate was 46 % in the hysteroscopy group and 40.43 % in the control group. (p-value= 0.326, RR= 1.16 [95%CI: 0.862 to 1.56]). Live birth rate was 41.28% in the hysteroscopic group and 31.93% in the control group (p-value=0.143, RR= 1.293 [95%CI: 0.916 to 1.825]). For those patients having surplus cryopreserved embryos, after 2 months, a second embryo transfer was performed. The cumulative LBR was 44.05% in the hysteroscopic group and 32.25% in the control group (p-value=0.029, RR= 1.368 [95%CI: 1.031 to 1.815], RD= 11.9% [95%CI: 1.2% to 22.3%] and NNT= 8 [95%CI: 4 to 85]). Conclusion: The current study clearly demonstrated a significantly higher cumulative live birth rate in the intervention group.